ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMECAHAN MASALAH KELAS VII DI SMPN 8 PONTIANAK - Saleni, Resti Mien; Hartoyo, Agung; Astuti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the level of students' critical thinking skills in problem solving on a quadrilateral subject. This is a qualitative descriptive study. The subjects of the study were students of grade IXB of SMP Negeri 8 Pontianak. Subjects were selected using purposive sampling. Data collection instruments are observation and critical thinking ability tests. Data were analyzed by classifying data in the level of critical thinking based on Ferret critical thinking indicators based on the four steps of Polya's problem solving. From a study of 26 students, students' critical thinking results were 7.7% for critical thinking, 26.9% for critical thinking, 65.4% for uncritical thinking. Highly capable students are able to reach the third level of thinking, which is critical. They are able to fulfill the 4 characters of critical thinking or only meet three characters of critical thinking with the provisions of K1 and K2 fulfilled. Students who are capable of level 2 thinking (sufficiently critical) are able to fulfill three or two characteristics of critical thinking. Students who are capable of level 1 (uncritical) level thinking only fulfill one of the critical thinking characters or even students do not fulfill all of the critical thinking characters available.Keywords: Critical thinking, Polya’s problem solving, Level of critical thinking